(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Fear is a critical welfare concern in poultry, often linked to reduced productivity. While growth and feed efficiency traits have been extensively studied in commercial broiler breeds, limited information exists on breed-specific differences in fear-related behaviors. This study evaluated fear responses in four broiler breeds using the tonic immobility (TI), inversion, and emergence tests at weeks 1, 2, and 3 of age. A total of 100 chicks (25 per breed), all from a common genetic background, were assessed. Results showed that emergence duration significantly differed by breed at all three time points, with Cobb 500 and Marshall generally emerging faster. Tonic immobility duration varied significantly by breed only at week 1, with Marshall exhibiting the longest duration. Inversion test results revealed significant breed effects across all weeks, with Marshall birds consistently showing the highest number of wing flaps, a strong fear indicator. Overall, Marshall chickens displayed the most pronounced fear responses across multiple tests and time points, indicating higher baseline fearfulness compared to other breeds. This study investigated breed-specific differences in fear behaviors among four commercial broiler breeds—Arbor Acres, Marshall, Ross 308, and Cobb 500—at weeks 1 to 3 of age. Using tonic immobility, inversion, and emergence tests, significant differences were observed in behavioral responses across breeds and ages. Marshall chickens exhibited the highest fear responses, as indicated by prolonged tonic immobility and increased wing flapping. The findings underscore the need to consider behavioral traits in broiler breeding programs to enhance welfare outcomes.